Diary of a wimpy kid: the deep end - Kinney , Jeff (Puffin London, 2021)
Greg Heffley and his family hit the road for a cross-country camping trip, ready for the adventure of a lifetime. But things take an unexpected turn, and they find themselves stranded at an RV park that's not exactly a summertime paradise. When the skies open up and the water starts to rise, the Heffleys wonder if they can save their vacation-or if they're already in too deep